Anthropogenic contamination of Portuguese coastal waters during the bathing season: Assessment using caffeine as a chemical marker. Issue 1 (15th July 2017) - Paíga, Paula; Delerue-Matos, Cristina
Abstract: Bathing water quality standards are based on international standards and legislations. However, in Europe, only the microbiological parameters are to be accomplished. Recent research has focused on chemical indicators that can determine human fecal contaminants in water. Therefore, the suitability of caffeine as a chemical marker of seawater pollution in the north Portuguese coastal area in the Atlantic Ocean during the bathing season was assessed in this study. The quality of water from the coasts of five cities was monitored. 101 seawater samples were collected from 14 beaches, and their water quality was classified as sufficient, good, and excellent. Caffeine was detected in all samples in concentration range of 18 to 525 ng/L. The highest average concentration of caffeine was found in seawater samples collected in July from beaches classified as having sufficient water quality, which were located in cities with high population density and high tourist affluence. Graphical abstract: Highlights: Assessment of pollution in the Portuguese coastal area in the Atlantic Ocean Evaluation of caffeine during the bathing season period in five cities Fourteen beaches classified with sufficient, good, and excellent water qualities were monitored. Caffeine was detected in all seawater samples with concentrations ranged from 18 to 525 ng/L. Efficacy of caffeine as a marker for human contamination in coastal waters was shown.